Product Photography Editorial On Instagram Feed @tuloladesigns - Putu Dudyk Arya Putra (Proceeding Bali-Bhuwana Waskita: Global Art Creativity Conference, 2021)
Abstract Instagram as a social networking platform that focuses on visual content such as photography and videography has attracted many users. Ease of access, numbers of features and wide reach make Instagram widely used as a promotional medium. Tulola Designs is one of Bali's local-based national brands that uses Instagram as the spearhead of its promotion. This company focuses on the production and sale of jewelry with Indonesian cultural characteristics carries out professional management on its Instagram account @tuloladesigns. There are two types of visual media uses by Tulola Designs on their Instagram, namely photos and videos. Scheduled uploads, conceptual photography and effective copy writing are the keys to give an image and identity to the products offered. The form of Tulola Designs’s promotion is carried out through the Instagram feature, namely feed posts, stories, and reels. In this paper the author focuses on the product photography editorial conducted by Tulola Designs on @tulola.designs instagram feed. The editorial role of product photography is described using a qualitative descriptive method. Visual material methods and online data search are used to reveal the technical and theoretical processes of product photography editorial so that in the end the goal of Tulola Designs’s promotion can be implemented properly and product value can be achieved. Keywords: Editorial, Product Photography, Instagram, Tulola Designs